The safety and effectiveness of commonly-marketed natural supplements for weight loss in populations with obesity: A critical review of the literature from 2006 to 2016. Issue 10 (30th May 2020) - Wharton, Sean; Bonder, Revi; Jeffery, Aaron; Christensen, Rebecca A. G.
Abstract: Objective: To evaluate the evidence published from 2006 to 2016 on the effectiveness and safety of commonly used natural supplements for weight loss in individuals with obesity. Methods: Amazon and Google were searched for names of mono-agent natural supplements marketed for weight loss and a list of the 10 supplements was created. Google Scholar, Pubmed, Science Direct, and the Cochrane Library were searched for articles that met inclusion. Results: At least one article was published on the effectiveness or safety of bitter orange, capsinoid, carnitine, chromium picolinate, Coleus forskohlii, conjugated linoleic acid, glucomannan, green tea and psyllium for weight loss in populations with obesity from 2006 to 2016. There was insufficient evidence to suggest that the natural supplements examined contribute to significant weight loss, with the exception of perhaps glucomannan in the form of PGX. In general, the majority of side-effects reported were minor to moderate, and gastrointestinal-related. However, in some cases extreme side-effects such as liver and kidney failure were observed. Conclusion : Contrary to popular belief, results of this review suggest that the use of natural supplements for weight loss are unlikely to contribute to meaningful weight loss and in some cases may contribute to harm.